STUDY OF ORGANOLEPTIC TESTING ON SPORT SHOE - Eka Legya Frannita; Erlita Pramitaningrum; Muhammad Charis Hidayatullah (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Currently sports shoes successfully attract a lot of consumers. Sports shoes were originally designed to support sports activities and reduce the risk of injury when doing sports. Nowadays, sports shoes are starting to be designed by adding an aesthetic value that increases fashion value. However, even though sports shoes have started to appear aesthetics side, the quality of the shoes is also an important factor when the shoes are used. To maintain the quality of shoes, it is necessary to test the quality of shoes. One of the important tests is organoleptic testing. The organoleptic testing can be carried out by following the requirements in accordance with SNI 12- 7072-2005 concerning fitness sports shoes with synthetic soles with a glue system, SNI 12-7075- 2005 about sports shoes with printed soles with a glue system, SNI 12-7195- 2006 about glue system jogging sports shoes, and SNI 12-7196-2006 concerning cross-country sports shoes. Several things that need to be considered are design aesthetics and workmanship inspection. This research focuses on conducting organoleptic test on eleven samples of sports shoes. Based on the results of tests that have been carried out based on SNI for sports shoes, there are several defects in five pairs of shoes.